SPITZER observations of z-3 Lyman break galaxies: Stellar masses and mid-infrared properties - Rigopoulou, D; Huang, J; Papovich, C; Ashby, M; Barmby, P; Shu, C; Bundy, K; Egami, E; Magdis, G; Smith, H; Willner, S; Wilson, G; et al. (Institute of Physics Publishing, 2006)
We describe the spectral energy distributions (SEDs) of Lyman break galaxies (LBGs) at z ∼ 3, using deep mid-infrared and optical observations of the extended Groth strip, obtained with IRAC and MIPS on board Spitzer and from the ground, respectively. We focus on LBGs with detections at all four IRAC bands, in particular the 26 galaxies with IRAC 8 μm band (rest-frame K-band) detections. We use stellar population-synthesis models and probe the stellar content of these galaxies. Based on best-fit continuous star formation models, we derive estimates of the stellar mass for these LBGs. As in previous studies, we find that a fraction of LBGs have very red colors and large estimated stellar masses (M* > 5 × 1010 M⊙); the current Spitzer data allow us, for the first time, to study these massive LBGs in detail. We discuss the link between these LBGs and submillimeter-luminous galaxies, and we find that the number density of these massive LBGs at high redshift is higher than predicted by current semianalytic models of galaxy evolution. © 2006. The American Astronomical Society. All rights reserved.